Diet-Induced Podocyte Dysfunction in Drosophila and Mammals. - Na, J.; Sweetwyne, M.T.; Park, A.S.; Susztak, K.; Cagan, R.L. (Cell reports, 2015)
Diabetic nephropathy is a major cause of end-stage kidney disease. Characterized by progressive microvascular disease, most efforts have focused on injury to the glomerular endothelium. Recent work has suggested a role for the podocyte, a highly specialized component of the glomerular filtration barrier. Here, we demonstrate that the Drosophila nephrocyte, a cell analogous to the mammalian podocyte, displays defects that phenocopy aspects of diabetic nephropathy in animals fed chronic high dietary sucrose. Through functional studies, we identify an OGT-Polycomb-Knot-Sns pathway that links dietary sucrose to loss of the Nephrin ortholog Sns. Reducing OGT through genetic or drug means is sufficient to rescue loss of Sns, leading to overall extension of lifespan. We demonstrate upregulation of the Knot ortholog EBF2 in glomeruli of human diabetic nephropathy patients and a mouse ob/ob diabetes model. Furthermore, we demonstrate rescue of Nephrin expression and cell viability in ebf2(-/-) primary podocytes cultured in high glucose.